CAPABILITY AND ARROGANCE EXACERBATE FINANCIAL STATEMENT FRAUD: EVIDENCE FROM INFRASTRUCTURE COMPANY IN INDONESIA - Anisa, Fitri; Rahmadhani, Sari (Jurnal Aplikasi Akuntansi, 2026)
This research examines financial statement fraud within Indonesia’s infrastructure, property, and real estate sectors. The study analyzes the influence of Pressure, Opportunity, and rationalization on fraud tendencies, while testing Capability and arrogance as moderating variables under the Fraud Pentagon framework. Using a quantitative approach, 236 observations from companies listed on the Indonesia Stock Exchange (2021–2025) were analyzed using PLS-SEM. Results indicate that Pressure and Opportunity significantly impact fraud potential. Furthermore, Capability and arrogance strengthen the Pressure to commit financial statement fraud. However, rationalization shows no significant effect, and neither Capability nor arrogance successfully moderates the relationship between opportunity or rationalization and fraud tendencies. These findings suggest that fraud in these sectors is primarily driven by external financial pressures and internal control weaknesses, exacerbated by managerial power and ego. This study implies that firms must enhance internal oversight and auditor quality to mitigate risks. These results provide critical insights for regulators and investors in evaluating corporate integrity within high-complexity industries.